2022
DOI: 10.1080/10494820.2022.2061007
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perception about the difficulty and use of programming and robotics in the classroom

Abstract: Programming and robotics are resources that can be used as a learning tool for understanding content. However, some teachers are unmotivated due to preconceptions about their difficulties, which hinder their learning and subsequent application in the classroom. This study aims to determine the perception of 195 teachers teaching different grade levels and areas of knowledge on the learning of programming, robotics, and their possibilities of applying them in the classroom. The results show no differences accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In short, these two conclusions draw researchers' attention to future TPD research that may help teachers to develop, implement and assess integrative learning activities based on cutting‐edge technologies like the use of robotics (Kim et al, 2015; Ortega‐Ruipérez & Lázaro Alcalde, 2022), or artificial intelligence (AI) in STEM education (Kim & Kim, 2022; Yang, 2022). Moreover, the researchers might also consider the shift to online or blended learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…In short, these two conclusions draw researchers' attention to future TPD research that may help teachers to develop, implement and assess integrative learning activities based on cutting‐edge technologies like the use of robotics (Kim et al, 2015; Ortega‐Ruipérez & Lázaro Alcalde, 2022), or artificial intelligence (AI) in STEM education (Kim & Kim, 2022; Yang, 2022). Moreover, the researchers might also consider the shift to online or blended learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching approaches play an important role in the design and implementation of robotics course activities (Ortega-Ruipérez & Lázaro Alcalde, 2022;Zhang et al, 2023). Previous studies indicated that the most common teaching approaches in robotics education include lecture-based learning, project-based learning, and cooperative learning (Cheng et al, 2013;Jung, 2013;Xia & Zhong, 2018;Zhong et al, 2019).…”
Section: Robotics Educationmentioning
confidence: 99%
“…However, owing to the limited knowledge and skills in engineering and technology fields, young students, especially primary school students, may have difficulty in accurately constructing robots. In addition, they are unable to quickly and directly make the connection between programming and the actions of robots and writing computer programs to drive robots (e.g., Ortega-Ruipérez & Lázaro Alcalde, 2022; Sullivan & Bers, 2016; Sullivan et al, 2013). These difficulties may affect students’ learning achievements and perceptions in robotics courses (e.g., Sullivan et al, 2013; Sullivan & Bers, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation